2009
DOI: 10.1163/156856108x388399
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobically Functionalized Chitosan Particles

Abstract: Particles of chitosan have a very polar surface, and thus they are easily wetted by water and also dissolve in acidic media. The hydroxyl and amino groups offer a high potential for grafting reactions. Aldehydes and carbonic acid derivatives were covalently grafted, preferably onto the amino groups. The reactions were carried out in solution as homogeneous phase reactions as well as on the particle surfaces as heterogeneous phase reactions. Covalently bonded alkyl chains impart the chitosan molecules with hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
0
13
1
3
Order By: Relevance
“…Model reactions previously carried out on CHS microparticles, showed that the grafting of bifunctional copolymers is more effective than the grafting of single molecules. [14,15] POMA was found to be the most convenient copolymer in comparison with other maleic anhydride copolymers and polymers bearing epoxy or sulfonic acid groups. [16] The anhydride groups of POMA are highly reactive to the amino groups of CHS and the long alkyl chains are able to form a closely packed hydrocarbon layer with terminal methyl groups lowering the surface polarity substantially.…”
Section: Resultsmentioning
confidence: 99%
“…Model reactions previously carried out on CHS microparticles, showed that the grafting of bifunctional copolymers is more effective than the grafting of single molecules. [14,15] POMA was found to be the most convenient copolymer in comparison with other maleic anhydride copolymers and polymers bearing epoxy or sulfonic acid groups. [16] The anhydride groups of POMA are highly reactive to the amino groups of CHS and the long alkyl chains are able to form a closely packed hydrocarbon layer with terminal methyl groups lowering the surface polarity substantially.…”
Section: Resultsmentioning
confidence: 99%
“…Für Pfropfreaktionen erscheinen wegen ihrer hohen Reaktivität gegenüber Carbonylverbindungen insbesondere die primären Aminogruppen des Chitosans geeignet [8]. Die Aminogruppen wurden aber auch genutzt, um über partielle Vernetzungsreaktionen mit bifunktionellen organischen Molekülen (z.…”
Section: Chemische Hydrophobierungunclassified
“…B. Säurechloride und -anhydride) an. An Modellreaktionen konnte mittels 13 C-CP-MAS-NMR-Spektroskopie gezeigt werden, dass eine Anbindung der Carbonsäuren an die Aminogruppen unter Ausbildung kovalenter Amidbindungen stattfand [8]. Die Umsatzgrade waren auch unter Verwendung von N,N'-Dicyclohexylcarbodiimid und Dimethylaminopyridin so gering, dass keine der so hergestellten Kompositoberflächen ultrahydrophobe Eigenschaften zeigte.…”
Section: Chemische Hydrophobierungunclassified
See 2 more Smart Citations